(untitled) (Brazilian Journal of Oceanography, 2019)
Embryonic malformations can be a result of exposure toxic substances (pollution), lack of nutrients, physical restraint, genetic disorders, or infections and diseases. Such malformations can be classified according to severity and offspring survival outside the uterus. Moreover, abnormalities are normally restricted to a small portion of the litter, mostly, to only one embryo. Here, we report a case of congenital malformation dominance in an offspring of the shortnose guitarfish and compare it with other abnormalities commonly reported in batoids in addition to discussing the possible causes involved in the observed deformities.